OPTIMALISASI PIDANA TAMBAHAN UANG PENGGANTI DALAM TINDAK PIDANA KORUPSI GUNA PENGEMBALIAN KERUGIAN KEUANGAN NEGARA - Julius Pieter Tobi William (2022)
The optimalitation of additional compensation money is still far from 'successful' due to several aspects, namely from preventive and repressive measures such as confiscation, confiscation and auction, state civil lawsuits against the defendant or the defendant's heirs if the defendant has died and the criminal subsidence of additional replacement money. Namely substitute imprisonment that has not achieved preventive, deterrent and reform of moral values of defendants of criminal acts of corruption. In supporting this writing, the author uses a normative juridical research method with qualitative descriptive analysis techniques, then uses a statutory and conceptual problem approach. Therefore, several concepts are needed to help increase of additional substitute money, in particular, such as auctions in the ongoing legal process and the decision is not yet legally binding, guidelines for benchmarking an ideal substitute imprisonment based on additional compensation for additional money and provisions for calculating the abolition of the remaining replacement imprisonment. for the payment of replacement money while serving the basic imprisonment and substitute imprisonment as well as adopting a state civil lawsuit with the concept of Non-Conviction Based (NCB) Asset Forfeiture. These concepts and guidelines will support Article 18 paragraph (1) letter b of Law Number 31 of 1999 as amended by Law Number 20 of 2001 concerning the Eradication of Criminal Acts of Corruption and Supreme Court Regulation Number 5 of 2014 concerning the Criminal Law of Additional Compensation. In the Crime of Corruption.